Optimalisasi Pengadaan Bahan Baku di PT. Trianugrah Metalindo Melalui Pendekatan Just In Time (JIT) - Mustofa, Muhammad (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to determine the3 most effective raw material procurement method at PT. Trianugrah Metalindo, by comparing the method used by the company with the just in time (JIT) method. This study uses a quantitative descriptive method so that it describes the numbers. From the analysis using the just in time method, it can be concluded that the just in time method is more effective in calculating the total cost of PT. Trianugrah Metalindo. The cost savings obtained were Rp. 3,246,039 from the initial inventory cost of Rp. 3,694,380.